Biological inspired self-organized secure autonomous routing protocol for wireless sensor networks [electronic resource] - Kashif Saleem; Norsheila Fisal, supervisor; Fakulti Kejuruteraan Elektrik (2011)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2011